1985
DOI: 10.1029/jc090ic06p11756
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations and rotations of elliptical warm‐core rings

Abstract: Exact analytical solutions are found to describe f plane time-dependent, elliptical warm-core rings where the interface intersects the surface along the periphery. The space variables can be eliminated to reduce the problem to a system of differential equations in time. The motion of the center of mass is resolved and subtracted. Small departures from circular shape have three intrinsic frequencies' two are inertial and superinertial, while the third is a low-frequency mode that corresponds to a slow rotation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 26 publications
3
67
0
Order By: Relevance
“…In the more general geophysical context, isolated vortices called 'rodons' (Cushman-Roisin et al 1985;Young 1986) have been found as exact solutions to the single-layer shallow-water equations (having a variable fluid depth), a model of warm-core rings shed by the Gulf stream. Płotka & Dritschel (2012) examined a wide class of vortex patch equilibria with uniform potential vorticity (PV) in the quasi-geostrophic (QG) shallow-water equations, determining both their equilibrium shapes and stability numerically.…”
Section: Introductionmentioning
confidence: 99%
“…In the more general geophysical context, isolated vortices called 'rodons' (Cushman-Roisin et al 1985;Young 1986) have been found as exact solutions to the single-layer shallow-water equations (having a variable fluid depth), a model of warm-core rings shed by the Gulf stream. Płotka & Dritschel (2012) examined a wide class of vortex patch equilibria with uniform potential vorticity (PV) in the quasi-geostrophic (QG) shallow-water equations, determining both their equilibrium shapes and stability numerically.…”
Section: Introductionmentioning
confidence: 99%
“…The relation (5.35) in the above is readily validated by symbolic computation and has an analog in the theory of the evolution of elliptical ocean warm-core eddies ( [8,14,32]). On elimination of θ − ϕ in (5.22) via the relation (5.32) and use of (5.37) is seen that,B is given by the elliptic integral relation…”
Section: An Elliptic Vortex Reduction To An Integrable Ermakov-ray-rementioning
confidence: 99%
“…On introduction of the Madelung transformation [25] 8) it is seen that the capillarity system (2.6)−(2.7) may be embodied in the NLS-type equation…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is related to when the vorticity is concentrated into elliptical form. While such a vortex can be deformed (stretch-shrink and rotate), the suggestion is that the elliptical shape should be maintained [6] [7] [8] [9].…”
Section: Introductionmentioning
confidence: 99%